غالؔب کا طیفِ تمنا - Shehr Bano Zafar; Dr. Saeed Ahmed (Khayaban - خیابان, 2023)
Ghalib's Poetry is deep and insightfull, we can appreciate his vision by noticing how he skillfully uses psychological concepts and phenomena in his poetry. Ghalib’s spectrum of aspiration is a fusion of such desires and longings as reflect of human’s glory. These psychological stimuli inseparably connected with urge aspiration and pleasure as influence human heart and mind direct. Unconscious plays very important role in shaping our deepest desires and wishes. According to Sigmund Frued it is the most essential part of mind. Our desires and imaginations are closely connected leading to a constant flow of strong desires with in our mind. The aspirations, urges and longings aroused from the imagination of a visionary poet like Ghalib can not be considered common and general. This article aims to highlight the wide ranging desires that have emerged from Ghalib’s "Taif-e-Tammna".